Practical Analysis of Stock Market Under ESG - Wang, Yiqi (International Journal of Global Economics and Management, 2024)
In today's era, climate change brought about by the greenhouse effect is gradually bringing more and more economic losses and natural disasters. In order to mitigate the negative impact of climate change, many countries have jointly formulated a 1.5°C climate scenario, which has brought a lot of impact on the global economy and industry development (Henderson et al., 2020). At the same time, my client commissioned me to build a portfolio that complies with the 1.5°C climate scenario, and the shares must be included in the S&P 500 Net Zero 2050 Climate Transition ESG Index as of 30/09/2022. The total portfolio is $100,000, and the benchmark designates the S&P 500 Net Zero 2050 Climate Transition ESG Index. Because the investment horizon is short and only six weeks, I chose semi-active management in my portfolio management process, and the rebalancing method was selected as percentage rebalancing. Finally, based on macro and industry analysis and relative valuation and technical analysis of the corresponding stocks, I selected ten stocks: Starbucks Corporation, Tesla, Inc., Amgen Inc., Cisco Systems, Inc., Eversource Energy, The Coca-Cola Company, and Expeditors International of Washington, Inc., Trans Digm Group Incorporated， Netflix, Inc., S&P Global Inc. I calculated their respective shares using the Markowitz model and bought and rebalanced, but unfortunately, my portfolio did not work as expected. The sector index fell by 4.87% in the week of the investment term, but my portfolio fell by 7.45% and performed poorly. Among them, the collapse of Tesla due to special events and my previous judgment of Tesla were greatly affected, and although its share price was only 9.94%, its share price fell by 33.74%. Although the late-stage rebalancing gave me hope for the better, the short investment horizon became a significant obstacle to the improvement of my portfolio.